FORMING ECONOMIC AMBIENCE OF THE BUILDING ENTERPRISE AND THEIR INFLUENCE UPON HIS (ITS) BEHAVIOUR MANAGEMENT - I. SH. Kurbanov (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
The problems of behavior management building enterprise are considered in sloppy problemsolvingambience. Happen to the different regularities of the interaction factor problem-solving ambience and their influence upon behavior of the building enterprise.